PJMHS 2022
DOI: 10.53350/pjmhs22162223
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Analysis of 75 Salivary Gland Tumors at Mayo Hospital, Lahore

Abstract: Aim: To describe the clinic-o-pathological pattern of patients presented with salivary gland tumors at Department of Maxillofacial surgery Mayo hospital Lahore during time period of one year from 1st January 2019 to 31st December 2019. Methods: This was a retrospective cross-sectional study conducted at Department of Oral and Maxillofacial Surgery, Mayo Hospital Lahore. 75 cases of Salivary gland tumors in the head and neck region were identified. Patient’s medical record and pathology reports were retrieved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Pleomorphic adenoma was the commonest benign neoplastic lesion in our study. Our findings are in accordance with a recent study by Mahmood et al 16 Parotid gland was the most common site of Pleomorphic adenoma in 67.7% of cases followed by submandibular gland in 17.6% of cases, a finding in line with the results of recently published studies from India 18 and the Netherland 19 . Though Warthin's tumor was found as a rare entity among benign salivary gland lesions in the present study; it has been reported as the second and the third most common benign tumor secondary to pleomorphic adenoma in two earlier studies 12,20 A recent study in Greece by Kadletz et al 21 reported a rising incidence of Warthin's tumor in recent years that has been correlated with obesity, alcohol consumption, and cigarette smoking.…”
Section: Discussionsupporting
confidence: 94%
“…Pleomorphic adenoma was the commonest benign neoplastic lesion in our study. Our findings are in accordance with a recent study by Mahmood et al 16 Parotid gland was the most common site of Pleomorphic adenoma in 67.7% of cases followed by submandibular gland in 17.6% of cases, a finding in line with the results of recently published studies from India 18 and the Netherland 19 . Though Warthin's tumor was found as a rare entity among benign salivary gland lesions in the present study; it has been reported as the second and the third most common benign tumor secondary to pleomorphic adenoma in two earlier studies 12,20 A recent study in Greece by Kadletz et al 21 reported a rising incidence of Warthin's tumor in recent years that has been correlated with obesity, alcohol consumption, and cigarette smoking.…”
Section: Discussionsupporting
confidence: 94%